Use of the 10‐Group Classification System to analyze how the population control policy change in China has affected cesarean delivery. Issue 2 (8th June 2017) - Zhang, Yihui; Gu, Ning; Wang, Zhiqun; Zheng, Mingming; Hu, Yali; Dai, Yimin
Abstract: Objective: To analyze the initial effect following the relaxation of China's population control policy on the cesarean delivery (CD) rate using the 10‐Group Classification System (TGCS). Methods: A retrospective study included all deliveries at a center in Nanjing, China, during 2014–2015. The deliveries were classified using the TGCS. The obstetric populations and the CD rates in each group were compared between 2014 and 2015. Results: Overall, 11 006 deliveries were analyzed. The overall CD rate increased from 28.3% (1623/5737) in 2014 to 33.8% (1782/5269) in 2015 ( P< 0.001). The largest contributor to the overall CD rate—accounting for approximately one‐third of all CDs—were nulliparous women with a single cephalic term pregnancy and induced labor or prelabor CD (group 2); the CD rate in this group increased from 27.2% to 31.4%. Moreover, the proportion of women with a single cephalic term pregnancy with previous CD (group 5) steeply increased from 6.4% to 10.4% of all deliveries; the CD rate in this group during 2014–2015 was 76.6%. Conclusion: With China ending its one‐child policy, the characteristics of the obstetric population changed. Women with a single cephalic term pregnancy with previous CD were the largest contributor to the CD rate increase. Abstract : Following the end of China's one‐child policy, single cephalic term pregnancies after previous cesarean delivery made the largest contribution to the increase in cesarean deliveries.